2017
DOI: 10.1021/acs.jmedchem.6b00648
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Discovery of Synthetic Agonists for the Zn2+-Sensing G-Protein-Coupled Receptor 39 (GPR39) Reveals Novel Biological Functions

Abstract: The G-protein-coupled receptor 39 (GPR39) is a G-protein-coupled receptor activated by Zn. We used a homology model-based approach to identify small-molecule pharmacological tool compounds for the receptor. The method focused on a putative binding site in GPR39 for synthetic ligands and knowledge of ligand binding to other receptors with similar binding pockets to select iterative series of minilibraries. These libraries were cherry-picked from all commercially available synthetic compounds. A total of only 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…In addition, we found the N-terminal domains played significant roles (Supplementary Figure S1A) in signaling [65], in agreement with the observation of the disulfide bridge between Cys11 and Cys191 maintaining the activity of GPR39 [32]. Inter-and intra-molecular interactions [66,67] are thus further indicated, warranting the exploration of additional interactors, modifications and structures of GPR39. The discovery of specific molecular sites and features for signaling would lead to biological understanding of the receptor and selective modulation of individual pathways.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, we found the N-terminal domains played significant roles (Supplementary Figure S1A) in signaling [65], in agreement with the observation of the disulfide bridge between Cys11 and Cys191 maintaining the activity of GPR39 [32]. Inter-and intra-molecular interactions [66,67] are thus further indicated, warranting the exploration of additional interactors, modifications and structures of GPR39. The discovery of specific molecular sites and features for signaling would lead to biological understanding of the receptor and selective modulation of individual pathways.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to the described role of Gpr39 in the NAcc, Gpr39 alterations in brain areas influencing depression and anxiety-like behaviors [12,13,22,23] could contribute to alcohol intake. Furthermore, a recent study showed that two other GPR39 agonists induced somatostatin release and inhibited ghrelin release in gastric mucosal cells [67]. Further evidence has shown that ghrelin inhibits water intake [68] by modulating angiotensin II [69], and ghrelin also stimulates alcohol intake [70][71][72].…”
Section: Discussionmentioning
confidence: 99%
“…Here we have applied the technology in a modified form in an academic setting, and successfully identified nanomolar agonists for GPR91 through the generation of two mini libraries of less than 250 compounds in total – while employing the synthesis of only a few novel compounds to solve the stereochemistry of receptor recognition. Recently we have applied the original site-directed approach to the Zn 2+ sensor GPR39 by using its endogenous ligand Zn 2+ [34] , [35] , [36] as an essential allosteric modulator to bring low-potency hits into the working range of the biological assays [37] . In the case of GPR91, our initial SAR analysis indicated that certain back-bone modifications of succinate were allowed and that the cis conformation of the backbone was preferred.…”
Section: Discussionmentioning
confidence: 99%